Value added and Financial Performance: a Case Study of Listed Manufacturing Companies in Sri Lanka - Priya, K.; Nimalathasan, B. (My University, 2013)
Valued Added (VA) is a recent financial tool that helps to determine the true shareholder wealth contribution of companies. VA application in companies is relatively new. In this study, an attempt has been made to analyze the VA and financial performance during 2006 to 2010 (05 years) financial year of listed manufacturing companies in Sri Lanka. For the purpose of this study, the data was extracted from the annual reports of sample companies. Correlation and multiple regression analysis are used for analysis. The results revealed that VA has a great impact on all financial performance ratios except ROI and ROE. Further NPVA, VAS and VAFA are significantly correlated with GPM, NPM, and ROA, which are significant 5 and 1 percent level of significance respectively.
Keywords: Value Added; Financial Performance; Value Added Ratios